Amadou Hampâté Bâ (1901-1991) and Mohandas Karamchand Gandhi (1869-1948): Two Apostles of Tolerance - Aggarwal, Kusum (Études littéraires africaines, 2021)
Hampâté Bâ and Gandhi, two thinkers emblematic of two distinct geographical, historical, cultural and religious locations exhibit commonalities that are thought provoking. Both demonstrate a common penchant for principles of tolerance and human dignity for all people, across barriers of caste, color and creed. Understandably, both came to be seen internationally as men of wisdom, as free spirits, resolute even in the face of their unsettling times. Indisputably, the path the two men chose reveals glaring dissimilarities : Gandhi, more than Hampâté Bâ, represented a challenge for the colonial administration. Yet what unites them, however, is their shared experience of territorial colonization, closely documented in their autobiographies, but also the ways in which both constructed their ideas of tolerance in conjunction with strands of Western thought. Alternately reading them together and against each other, this essay seeks to uncover the imbrications that connect their trajectory and their thinking.